Two Birds One Stone: The Neuroprotective Effect of Antidiabetic Agents on Parkinson Disease-Focus on Sodium-Glucose Cotransporter 2 (SGLT2) Inhibitors - Kai-Jung Lin; Tzu-Jou Wang; Shang-Der Chen; Kai-Lieh Lin; Chia-Wei Liou; Min-Yu Lan; Yao-Chung Chuang; Jiin-Haur Chuang; Pei-Wen Wang; Jong-Jer Lee; Feng-Sheng Wang; Hung-Yu Lin; et al. (MDPI AG, 2021)
Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease affecting more than 1% of the population over 65 years old. The etiology of the disease is unknown and there are only symptomatic managements available with no known disease-modifying treatment. Aging, genes, and environmental factors contribute to PD development and key players involved in the pathophysiology of the disease include oxidative stress, mitochondrial dysfunction, autophagic-lysosomal imbalance, and neuroinflammation. Recent epidemiology studies have shown that type-2 diabetes (T2DM) not only increased the risk for PD, but also is associated with PD clinical severity. A higher rate of insulin resistance has been reported in PD patients and is suggested to be a pathologic driver in this disease. Oral diabetic drugs including sodium-glucose cotransporter 2 (SGLT2) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists, and dipeptidyl peptidase-4 (DPP-4) inhibitors have been shown to provide neuroprotective effects in both PD patients and experimental models; additionally, antidiabetic drugs have been demonstrated to lower incidence rates of PD in DM patients. Among these, the most recently developed drugs, SGLT2 inhibitors may provide neuroprotective effects through improving mitochondrial function and antioxidative effects. In this article, we will discuss the involvement of mitochondrial-related oxidative stress in the development of PD and potential benefits provided by antidiabetic agents especially focusing on sglt2 inhibitors.